2013
DOI: 10.1590/s1806-83242013005000033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different solutions on color stability of acrylic resin-based dentures

Abstract: The aim of this study was to evaluate the effect of thermocycling and immersion in mouthwash or beverage solutions on the color stability of four different acrylic resin-based dentures (Onda Cryl, OC; QC20, QC; Classico, CL; and Lucitone, LU). The factors evaluated were type of acrylic resin, immersion time, and solution (mouthwash or beverage). A total of 224 denture samples were fabricated. For each type of resin, eight samples were immersed in mouthwashes (PlaxColgate, PC; Listerine, LI; and Oral-B, OB), be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 25 publications
2
35
1
3
Order By: Relevance
“…20,26,27 In addition, in the literature, it is also possible to find some authors who report a ΔE <3.7 for a clinically acceptable color change of a material. 5,[21][22][23] In the present study, the color alteration in each group was lower than 3.3 (►Table 1). Therefore, both groups showed clinically acceptable values.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…20,26,27 In addition, in the literature, it is also possible to find some authors who report a ΔE <3.7 for a clinically acceptable color change of a material. 5,[21][22][23] In the present study, the color alteration in each group was lower than 3.3 (►Table 1). Therefore, both groups showed clinically acceptable values.…”
Section: Discussioncontrasting
confidence: 43%
“…This system can be calculated according to the formula: ΔE = [(ΔL) 2 + (Δa) 2 + (Δb) 2 ] ½ . [5][6][7]14,15,17,[19][20][21][22][23] The "L" represents brightness from 0 (black) to 100 (perfect white), the "a" represents the amount of red (positive values) or green (negative values), and the "b" represents the amount of yellow (positive values) or blue (negative values). 5,7,17,21,23 Color readings were taken before and after accelerated aging.…”
Section: Color Stability and Shore A Hardness Testsmentioning
confidence: 99%
“…but colour and colour stability is one of the major issues in anterior restorations. The colour stability of the restorations can be affected by several factors like surface roughness, absorption of fluids, accumulation of stains, dissolution, erosion by beverages, and degradation of the material (Goiato et al, 2013;Moon, Powers and Kiat-amnuay, 2014) Colour assessment can be done either by visual examination using shade guides or by using spectrophotometry. This visual examination is subjective to physiological and psychological factors based on the surrounding light.…”
Section: Discussionmentioning
confidence: 99%
“…There are various interim restorative materials available. Polymethyl methacrylate (PMMA) is one of the most commonly used denture base material(sepúlveda-navarro et al, 2011) (Goiato et al, 2013).The types of PMMA resin includes heat-cured resin, auto-polymerizing acrylic resin, light-cured resin, microwave processing resin, computer-aided design/computer-aided manufacturing (CAD/CAM) PMMA block resin (Tuna et al, 2013;Choi et al, 2018). The most commonly used PMMA resins are heat cured and CAD-CAM resin.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies also reported color change of acrylic resin when submitted to different cleansing solutions. [26,27] Both disinfection methods were performed at an elevated temperature, which could induce an additional monomer release that could interact with the glaze coat, thus, increasing the chromatic alteration [ Table 2]. The period of use can alter or remove this external coating, [28] but it is believed that the glaze underwent a chemical reaction from the increased temperature or disinfection methods.…”
Section: Discussionmentioning
confidence: 99%